2020
DOI: 10.1016/j.heliyon.2020.e04969
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration in the bio-edaphic ecosystem of National Highway-27 in Guwahati, Assam, India

Abstract: Vehicular pollution in cities is engendering the need to enhance the sequestration of CO 2 through bio-edaphic factors, such as trees and soil. Hence, this pioneering study aimed to analyze the interdependencies of the bio-edaphic ecosystem during carbon sequestration on a national highway in Guwahati, Assam, India. To quantify the tree carbon stock, soil physicochemical properties, soil nutrients, bulk density, organic carbon, and soil carbon stock, trees with diameters at breast height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 98 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…In our study, the top layer in the coniferous group held the highest SOCC (Table 1). Due to the input of nutrients from vegetation and artificial management, the content of organic carbon in the surface layer of soil is usually high, which exhibits a dynamic interaction with biological and anthropogenic activities [56,57]. Therefore, in cities, soils under coniferous trees, especially the upper layer, can provide greater potential for organic carbon storage.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the top layer in the coniferous group held the highest SOCC (Table 1). Due to the input of nutrients from vegetation and artificial management, the content of organic carbon in the surface layer of soil is usually high, which exhibits a dynamic interaction with biological and anthropogenic activities [56,57]. Therefore, in cities, soils under coniferous trees, especially the upper layer, can provide greater potential for organic carbon storage.…”
Section: Discussionmentioning
confidence: 99%
“…In general, most of the TEs showed a significant positive correlation (R 2 = 0.829) between OC of top soil samples and sampling location from the NH. On contrary, Bhattacharya et al (2020) reported that soil organic carbon significantly decreases with increasing distance from the NH when the experiment was conducted alongside NH-27 in Guwahati district of Assam, India. The increasing trend of OC in this study as a function of sampling distance from NH could be due to different environmental factors, vehicular movement, geographical locations, and choice of tea cultivars coupled with soil organic carbon management strategies adopted by the tea growers (Wang et al 2010).…”
Section: Organic Carbon (Oc)mentioning
confidence: 86%
“…The total biomass of trees varied positively and linearly with diameter at breast height (r = 0.953) by Bohre et al [19]. According to Bhattacharya et al [20] there was a positive correlation between carbon stock and tree biomass (r = 0.865). Behera et al…”
Section: Strength Of Association Between Carbon Sequestration and Dif...mentioning
confidence: 95%